Analysis interconnection level index marker by endothelial NOS, hypoxia and dysfunction in the pathogenesis of experimental diabetic retinopathy - Sirman, Ya. V.; Savytskyi, I. V. (Journal of Education, Health and Sport, 2020)
The aim of the study was to analyze changes in erythrocyte diphosphoglycerate levels and Willebrand factor in the development of hypoxia and endothelial dysfunction in experimental diabetic retinopathy. The study was performed on white Wistar rats weighing 180-200 g. Our results indicate the development of hypoxia on the 30th day of development of experimental diabetic retinopathy with subsequent progression of pathological changes on the 60th and 180th day of the study, as evidenced by the decrease level of 2,3 diphosphoglycerate of erythrocytes in the 2nd group (p <0,001). The most pronounced increase in the studied marker of hypoxia was detected in the 3rd stage of the experiment (p <0,001). As a result of our study, a violation of the structural and functional state of the endothelium in experimental diabetic retinopathy was proved, as evidenced by an increase in the level of Willeband factor in group 2 (p <0.001), most pronounced in stage 3. The most pronounced increase in the level of Willebrand factor was detected in the 3rd stage of the experiment (p <0.001). Analyzing the data obtained, we can say that there is a relationship between the development of hypoxia and endothelial dysfunction in the pathogenesis of experimental diabetic retinopathy.